Motives Behind the Transfer of a Bank From Conventional Banking to Islamic Banking in Pakistan - MUHAMMAD ASIF; UMAIR AHMED; MUHAMMAD ZAHID; AMIR KHAN (Journal of Business & Tourism, 2021)
The increasing awareness on Islamic banking and finance has created a huge demand for Shari’a based or Shari’a compliant products. Banks, especially are trying to capture this huge market by either converting themselves into a full fledge Islamic banks or opening a window for the Islamic based transactions. This study highlights the reasons why traditional banks turned towards Islamic model. The phenomenon of traditional banks turning into Islamic form was reinforced by the success of these banks averting the recent world economic crises. For data collection 80 respondents were selected, a proxy of five variables were undertaken as measurement. Variables of the study were:Transfer to Islamic Banking(TIB) was taken as dependent variable whileShari’a compliance(SC), Risk and Return(RR), Customer need(CN) and Performance of Islamic banks(PI) were taken as independent variables for which adopted questionnairewas used for data collection. The result of this research is that the banks are transferring from conventional banking to Islamic banking is just because of Shari’a Compliance, performance of Islamic banks and customer need for Islamic product.